Implementación del control interno basado en la metodología del coso III para mejorar la cartera de créditos de alto riesgo en a Caja Municipal de Ahorro y Crédito Horizonte S.A. - Pérez Li, Jorge Luis (2017)
ABSTRATC The present investigation aims to determine the influence of the document "Coso III - Integrated Internal Control Framework", published in 2013 by the Committee of Sponsoring Organizations of the Treadway Commission, which is a design risk management and internal control and which one proposes to improve the Credit portfolio of High Risk To develop this research, a sample of the population of Municipal Savings and Credit, adequate and representative of it, which was subjected to established research design, focusing the analysis on the components of the COSO Report III to determine whether it contributes to providing assurance that the internal controls designed to the lending process are effective and allow to improve the Credit portfolio of High Risk. Investigation and analysis concludes that the Municipal Savings and Credit Horizonte S.A. not the system of internal control based on the COSO III report, which does not allow early detection of deficiencies in the allocation process because of a lack of a rigorous evaluation to identify risks and select between alternative possible response to: avoid reduce, share or accept the risk, creating bad loans. Additionally it is recommended to implement the system of internal control over the components of COSO III report and submit to periodic review in order to ensure its efficiency and effectiveness.